Altered landing mechanics are shown by male youth soccer players at different stages of maturation - Read, P. J.; Oliver, J. L.; Myer, G. D.; De Ste Croix, M. B. A.; Belshaw, A.; Lloyd, R. S. (Physical Therapy in Sport, 2018)
Objectives: Examine the effects of maturation on single leg jumping performance in elite male youth soccer players. Design: Cross sectional. Setting: Academy soccer clubs. Participants: 347 male youth players classified as either pre, circa or post-peak height velocity (PHV). Main outcome measures: Single leg countermovement jump (SLCMJ) height, peak vertical landing forces (pVGRF), knee valgus and trunk side flexion. Results: Vertical jump height and absolute pVGRF increased with each stage of maturation (p<0.001; d=0.85-2.35). Relative to body weight, significantly higher landing forces were recorded on the left leg in circa versus post-PHV players (p<0.05; d=-0.40). Knee valgus reduced with maturation but the only notable between-group differences were shown in post-PHV players (p<0.05; d=0.67); however, greater ipsilateral lateral trunk flexion angles was also present and these differences were significantly increased relative to circa-PHV players (p<0.05; d=0.85). Conclusion: Periods of rapid growth are associated with landing kinetics which may heighten injury risk. While reductions in knee valgus were displayed with maturation; a compensatory strategy of greater trunk lateral flexion was evident in post-PHV players and this may increase the risk of injury.